Kajian Lafadz Taubah dan Inabah Dalam Al-Qur’an (Aplikasi Teori Anti Sinonimitas Muhammad Syahrur) - Muhammad Uzairon Salim (Cerdika: Jurnal Ilmiah Indonesia, 2026)
The Qur'an, as a universal and timeless guide, continues to be interpreted through various approaches, including contemporary linguistic perspectives. One of the ongoing debates in Qur’anic studies concerns the concept of synonymity, particularly the theory of anti-synonymity proposed by Muhammad Syahrur, who argues that no two words in the Qur’an share identical meanings. This study aims to examine the discourse of anti-synonymity theory and analyze its application in distinguishing the meanings of the terms taubah and in?bah in the Qur’an. This research employs a qualitative approach with a library research method, utilizing primary and secondary sources, and applying a linguistic analytical framework, including syntagmatic and paradigmatic analysis. The findings reveal that taubah refers to returning to God after committing sins, characterized by regret, repentance, and a commitment to moral improvement. In contrast, in?bah emphasizes a continuous spiritual return to God based on devotion, submission, and awareness, not necessarily linked to sin. The study concludes that the two terms are not synonymous but represent distinct spiritual concepts, thereby supporting Syahrur’s anti-synonymity theory. This research contributes to a deeper understanding of Qur’anic linguistic nuances and encourages more critical and contextual interpretations of sacred texts